EVALUATING SCIENCE LEARNING ASSESSMENTS: ALIGNING 21ST-CENTURY SKILLS AND LOCAL WISDOM FOR FUTURE TEACHERS IN 5.0 - Binar Ayu Dewanti; Kiki Septaria; Silvi Rosiva Rosdiana; Durrotul Afiyah (Universitas Bhinneka PGRI, 2025)
Recently, Indonesian higher education has redesigned curricula under the Merdeka Belajar-Kampus Merdeka (MBKM) policy to enhance student proficiency. This comprehensive framework covers learning outcomes, materials, processes, and assessment, with effective evaluation crucial for gauging learning outcomes and engaging students. This study explores the need for assessments based on local wisdom in science education to measure 21st-century skills for prospective teachers in Society 5.0. Using qualitative exploratory methods, the research involved interviews and document analysis with faculty from Universitas Islam Lamongan's Science Education Program. The findings reveal that while current assessments use diverse methods and address some 21st-century skills, they require better integration of local wisdom and consistent standards. Challenges include insufficient understanding of local wisdom integration, varied student competencies, and a lack of practical, context-driven strategies. The study recommends developing holistic assessments that incorporate local wisdom, practical experiences, and technology.